The Role of E-SPT Application in Moderating the Influence of Tax Sanctions, Service Quality, and Tax Awareness on Taxpayer Compliance - Salman, Kautsar Riza; Pratiwi, Eka (INDONESIAN JOURNAL OF SUSTAINABILITY, 2023)
Taxes are mandatory contributions to the state that are owed to individual and corporate taxpayers that are coercive by law and do not receive compensation directly and are used for the needs of the state for the greatest prosperity of the people. This study aims to examine and analyze the variables of tax sanctions, service quality and tax awareness of taxpayer compliance with the application of E-SPT as a moderation variable. The research method used in this study is a quantitative research method with primary data obtained from distributing questionnaires. The population in this study are individual taxpayers at KPP Pratama Bojonegoro. The sampling method used is convenience sampling. The sample for this research is 106 individual taxpayers. Data and processed using PLS-SEM with Warp-PLS 8.0 software. The results of this study state that tax sanctions have a positive and insignificant effect on taxpayer compliance, service quality has a positive and significant effect on taxpayer compliance, tax awareness has a positive and significant effect on taxpayer compliance, the application of E-SPT can moderate the effect of tax sanctions on taxpayer compliance, and the application of E-SPT can moderate the effect of service quality on taxpayer compliance.